Spatiotemporal Regulation of Transcript Isoform Expression in the Hippocampus - Park, Joun; Farris, Shannon (Frontiers in Molecular Neuroscience, 2021)
Proper development and plasticity of hippocampal neurons require specific RNA isoforms to be expressed in the right place at the right time. Precise spatiotemporal transcript regulation requires the incorporation of essential regulatory RNA sequences into expressed isoforms. In this review, we describe several RNA processing strategies utilized by hippocampal neurons to regulate the spatiotemporal expression of genes critical to development and plasticity. The works described here demonstrate how the hippocampus is an ideal investigative model for uncovering alternate isoform-specific mechanisms that restrict expression of transcripts in space and time.